Improving Early Childhood Cooperation Ability Through Whirlwind Games at Rodhatul Athfa: Meningkatkan Kemampuan Kerjasama Anak Usia Dini Melalui Permainan Angin Puyuh Di Rodhatul Athfa - Iqvina Hima; Agus Salim (Universitas Muhammadiyah Sidoarjo, 2022)
Developing the cooperative ability of preschoolers is an important milestone for a child's social development process. Experiences at school become a place for students to discuss agreements with groups of children or their peers. Based on the research there are 70% of the students are still not capable in terms of social skills so that this research aims to increase the ability of cooperation in students. The approach used in this research is Classroom Action Research which is carried out in three stages, namely Pre-cycle, Cycle I and Cycle II in order to obtain results in accordance with the assessment. At the Pre-cycle stage, the average score obtained by students was 42%, while at the Cycle I stage an average score was increased by 63%, which means that the average value is still not in accordance with the achievement target of the assessment, so the research is continued in the Cycle stage. II, after the Cycle II stage, the average value increased significantly, which was 87%. This can be seen from the comparison at each stage of the cycle during the research carried out. From the results obtained there is an increase which proves that through the Whirlwind Game can improve the ability of cooperation in children.